EFEKTIVITAS PELAKSANAAN PROGRAM PENGHAPUSAN SANKSI ADMINISTRASI DENDA PAJAK KENDARAAN BERMOTOR PADA UNIT PELAKSANA TEKNIS SAMSAT SIGI - Christian Surya Tandigala; Ahmad Sinala; Ani Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Christian Surya Tandigala, Stambuk Number B102 22 054, with the research title Effectiveness of the Implementation of the Motor Vehicle Tax Penalty Administration Sanctions Elimination Program at the Samsat Sigi Technical Implementation Unit, supervised by Ahmad Sinala and Ani Susanti. This study aims to determine the Effectiveness of the Implementation of the Motor Vehicle Tax Penalty Administration Sanctions Elimination Program at the Samsat Sigi Technical Implementation Unit. This study used a method with qualitative descriptive data. The research location is located at the Samsat Sigi Technical Implementation Unit Office. The theory used in this study is the theory proposed by Dunncan. The informants in this study amounted to 5 (five) people. The data obtained in this study are from observations, interviews, and documentation. Data analysis methods are Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing / Verification The results of this study show that the implementation of the Motor Vehicle Tax Penalty Administration Sanctions Elimination Program at the Samsat Sigi Technical Implementation Unit has not been effective as a whole, this is due to the non-achievement of the Integration indicator from the results of the study it is known that from the aspect of internal and external coordination has not been effective, the Adaptation indicator consisting of aspects of Tax Collector Officer Resources, not yet adequate. Second, Tax Collection Facilities, especially those related to the Application, The computerized system has not been optimal so that the management of tax revenue data and information has not been effective.